PENERAPAN MODIFIKASI PELURU MENGGUNAKAN BOLA KASTI UNTUK MENINGKATKAN KETERAMPILAN TOLAK PELURU SISWA KELAS IV SD NEGERI 137698 TANJUNGBALAI - WAHIDIN . (JURNAL ILMIAH KOHESI, 2018)
This study aims to improve the skills and activities of students performing bullet movements by applying bullet modifications using a ball in grade IV SD Negeri 137698 Tanjungbalai. Research is a classroom action research for two cycles. The subjects were all fourth grade students of SD Negeri 137698 Tanjungbalai academic year 2017/2018 which amounted to 31 students. The success of the study was determined by the criteria of at least 85% of students obtaining mastery with minimal mastery criteria (KKM) of 70. The results showed that learning by modification of bullets using a ball can improve the mastery of students 'bullets that marked by students' learning mastery improvement every cycle , that is, at the completion stage the mastery increased from 67% to 90%, at the completion stage of the mastery increased from 70% to 87%. And in the final stages of mastery increased from 41% to 90% so that in cycle II all aspects have reached the criteria of research success. Learning by modifying the bullet using the ball can also increase the learning activity of student's shot-to-student learning activities according to the observation of cycle I to cycle II, among others, the discipline to get the percentage of active students from 39% to 87%, earnestness get the percentage of active students from 68% to 87% , the responsibility of obtaining the percentage of active students from 48% to 90%, then enthusiastic students get the percentage of active students from 52% to 90% so that in cycle II all aspects have reached the criteria of research success.